Design of an adaptable 3D printed gripper - Sundar Vishanth (2016)
Picking, placing and manipulation of objects is a common task in most industries. The grippers available for this purpose are plenty and vary with the requirements. The amount of effort put in designing these grippers to make them suit the specific need is also a considerable. This project aims to reduce this time and effort by modifying and proposing a design of a Universal gripper. It also aims to study into the reasons for the limitations of the existing design and proposing an alternate design which would improve the functionality of the gripper. The proposed solution would cause to reduce the amount of effort and time required to design and modify grippers in industries and can be completely 3D printed so as to reduce the fabrication time, installation time and effort in using the gripper. The jamming gripper is a passive universal gripper that still has a few limitations from it becoming a more widely used gripper and is the gripper under consideration in this project. During this project, various tests have been conducted to observe the functionality of the jamming gripper and to suggest changes where possible. The test results prove the universality of the jamming gripper but also highlight a few of its drawbacks. Alternate jamming material and design for the jamming gripper have also been proposed as a mean of making the jamming gripper more sturdy and compatible for a regular and rough use. The current drawbacks in the field of 3D printing in terms of printing flexible material has also been discussed. The future scope of the project and various possible areas where the jamming gripper can be worked on, has also been mentioned.